Post-thrombotic syndrome prevention – do we really know the predictive factors? - Urbanek, Tomasz (Phlebologie, 2019)
Despite an increasing knowledge and experience regarding deep vein thrombosis (DVT) treatment, the rate of post-thrombotic syndrome (PTS) remains still relatively high. According to the current knowledge it is still difficult to predict on the individual basis, who of the DVT patients will develop PTS as late complication of the vein thrombosis. Among the factors influencing the higher prevalence of PTS, the ipsilateral DVT recurrence is of the highest importance. The other factors which should be mentioned are age, obesity, previous chronic venous disease as well as a proximal DVT location or lack of symptoms’ resolution in the early treatment. Looking for the most effective PTS prevention method several clinical trials were performed regarding pharmacological DVT treatment, use of early mobilization and medical compression stocking as well as an implementation of the thrombectomy and thrombolysis. This paper presents a review of the current knowledge regarding the PTS predictive factors and prevention.
Keywords: post-thrombotic syndrome; deep vein thrombosis; predictive factors; anticoagulation; compression; thrombolysis